Tradisi Perkawinan pada Masyarakat Desa Tanete Kecamatan Tompobulu Kabupaten Gowa - Syamhari; Ummu Kalsum (Universitas Islam Negeri Alauddin Makassar, 2024)
This research examines the Marriage Tradition in the Tanete Village, Tompobulu Subdistrict, Gowa Regency. The problem in this research is how the marriage tradition is conducted in the Tanete Village community, Tompobulu Subdistrict, Gowa Regency. The type of research used in this study is field research or field research using a descriptive research method. The data sources for this research were obtained from informants through interviews and direct observations. The data in this research include interview results and written data obtained through observations, field notes, interviews, and documentation. The data processing and analysis techniques are carried out through three stages: identifying data, grouping data, and describing data. The research findings are as follows: firstly, the marriage tradition in the Tanete Village community, Tompobulu Subdistrict, Gowa Regency, is carried out with a sequence of Abboya (proposal), the tradition of Abboya in the Makassar community, especially in Tanete village, is one of the traditions in marriage that needs to be preserved because this tradition is a form of diversity in community life. Appatantu Allo (determining the wedding day), in the Tanete Village community, Tompobulu Subdistrict, Appattantu Allo is a fundamental part of the marriage tradition carried out before the marriage contract process takes place because it is related to choosing an auspicious day, which holds special significance according to the local community's perspective.